THE LEVEL OF PUBLIC KNOWLEDGE ABOUT THE USE OF TRADITIONAL MEDICINE - Rifkarosita Putri Ginaris; Esa Aji Pratama; Alfina Nurrahman (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2024)
Traditional medicine is defined as an herb that has been used for generations for treatment. Ignorance about the use of traditional medicine leads to public misunderstanding of traditional medicines that are supposed to cure but are actually potentially harmful. This study aims to determine the level of public knowledge about the use of traditional medicine in Gondosuli Village, Tawangmangu District. The research method used the Spearman Rank test to determine the relationship between variables and correlations using 357 samples by random sampling. The results obtained showed a significant relationship between knowledge and the use of traditional medicine in Gondosuli Village, Tawangmangu, Karanganyar with a p value of <0.05, which was 0.000. The conclusion of this study is that community knowledge is related to the use of traditional medicine in Gondosuli village.